Examining Predictors of Mexican American Adolescents' Coping Typologies: Maternal and Paternal Behaviors and Adolescent Gender. (April 2017) - Cavanaugh, Alyson M.; Supple, Andrew J.; Stein, Gabriela Livas; Helms, Heather M.; Plunkett, Scott W.; Sands, Tovah
This study used latent profile analysis to develop coping typologies of 340, 14- to16-year-old Mexican American adolescents ( M = 14.46, SD = 0.69). Three typologies were identified: (a) opposition coping (adolescents who tended to use anger and venting emotions), (b) support-seeking coping (adolescents who relied on seeking support), and (c) escape and opposition coping (adolescents who relied on anger, venting, substance-use coping, behavioral avoidance, and peer support). Three key parental behaviors (support, knowledge, psychological control) of mothers and fathers and adolescent gender were examined as predictors of the coping typologies. Results indicated that parental support and knowledge, particularly from mothers, predicted membership into the support-seeking coping typology relative to the other two typologies. Girls were more likely than boys to utilize support-seeking coping than opposition coping. Gender socialization norms that may have influenced these results are discussed.